أثر جودة الخدمات الإلكترونية على ولاء العميل دراسة حالة مؤسسة موبيليس - أيوب بلوطار (My University, 2022)
This study aimed to show the correlation and influence between the quality of electronic services and customer loyalty. This study contained two parts, the first part dealt with the theoretical side in which the study variables were explained, the quality of electronic services as an independent variable, and customer loyalty as a dependent variable. Where the student relied mainly on distributing a questionnaire to a sample of 40 individuals, all of which were retrieved and subject to statistical analysis, with a response rate estimated at 100%. After the analysis process, which was relied on the statistical program SPSS, this study came to the following: There is a clear perception among the respondents about the quality of electronic services on customer loyalty in the institution under study.  The study showed that there is a positive correlation between the quality of electronic services and customer loyalty.  The study also showed that there is an effect between the quality of electronic services and customer loyalty. .......................................... هىدفت هذه الدراسة إلى تبيان علاقة الارتباط و التأثير بين جودة الخدمات الالكترونية وولاء العميل. وقد احتوت هذه الدراسة على جزأين، الجزء الأول تناول الجانب النظري الذي تم فيه شرح متغيرات الدراسة، جودة الخدمات الالكترونية كمتغير مستقل، وولاء العميل كمتغير تابع، أما الجزء الثاني فقد خصص للدراسة الميدانية التي تمت في وكالة موبيليس وحدة سوق أىراس . – - حيث اعتمد الطالب بشكل أساسي على توزيع استبيان على عينة مكونة من 40 فرد تم استردادها كلها وقابلة للتحليل الاحصائي بنسبة استجابة قدرت ب100 بالمائة بعد عملية التحليل التي تم الاعتماد فيها على البرنامج الاحصائي توصلت هذه الدراسة الى:  هناك تصور واضح لدى المبحوثين حول جودة الخدمات الالكترونية على ولاء العميل في المؤسسة قيد الدراسة.  أظهرت الدراسة أن هناك علاقة ارتباط موجبة بين جودة الخدمات الالكترونية وولاء العميل .  كما أظهرت الدراسة أن هناك تأثير بين جودة الخدمات الالكترونية وولاء العميل .